Whither (Not Wither) Copyleft (Journal of Open Law, Technology & Society, 2017)
This article contains an edited version of Professor Eben Moglen’s speech at the SFLC Fall Conference 2016. It explores the topic of Copyleft, enforcement and community engagement from the perspective of one of the key individuals in the rise of Free and Open Source Software from interesting idea to a central pillar of the global technology industry.